The Oral-Skin Axis in Autoinflammation: A Case Report of Severe Refractory Generalized Pustular Psoriasis (GPP) Resolved by Comprehensive Periodontal Intervention - Ni Putu Wina Widyastuti; Prima Sanjiwani Saraswati Sudarsa; Herman Saputra; Handelia Phinari; Luh Putu Venny Cempaka Sari; Kevin Jonathan Djuanda; Mario Korwa (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Generalized pustular psoriasis (GPP) is a severe, IL-36-driven autoinflammatory dermatosis, distinct from psoriasis vulgaris. Chronic periodontitis (CP) is a dysbiotic inflammatory disease sharing pathogenic pathways (IL-1, IL-17). An "oral-skin axis" has been hypothesized, but definitive clinical evidence of CP driving a GPP flare is scarce. Case presentation: We present a 37-year-old male with a history of plaque psoriasis who developed a severe, refractory GPP flare (GPPASI 35.8) with high-grade fever (38.9°C), profound neutrophilic leukocytosis (22.5 x 10³/µL), and markedly elevated CRP (150 mg/L). The flare was resistant to maintenance methotrexate. Workup revealed severe CP with multiple periapical abscesses, culture from which grew Porphyromonas gingivalis and Fusobacterium nucleatum. The patient underwent a comprehensive dental intervention, including emergency extractions and full-mouth debridement, with concurrent peri-operative Amoxicillin-Clavulanate therapy. This combined intervention led to a rapid resolution of fever, neutrophilia, and cutaneous pustulation within 72 hours, without any escalation of systemic immunomodulators. He achieved complete remission (GPPASI 1.0) at 3-month follow-up. Conclusion: This case provides a strong temporal association supporting the oral-skin axis, highlighting severe periodontitis as a potent trigger and amplifier for GPP. The rapid resolution following a combined surgical and antibiotic intervention suggests that targeting the oral inflammatory and microbial reservoir is a critical, actionable strategy. We strongly recommend consideration of a comprehensive dental/oral screening in patients with refractory GPP.